Glycemic Control Status as a Predictor of Blood Pressure in Patients with Type 2 Diabetes Mellitus - Hasan, Juliano Fadran; Setianingrum, Elisabeth Levina; Lada, Christina Olly; Handoyo, Nicholas Edwin (FORIKES, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder with a rising global prevalence and is frequently accompanied by hypertension. Adequate glycemic control plays a crucial role in preventing elevated blood pressure among patients with T2DM. This study aimed to compare systolic and diastolic blood pressure between patients with controlled and uncontrolled glycemic status. An analytical cross-sectional design was employed involving 71 patients with T2DM from three primary healthcare centers. Data were collected through measurement of glycated hemoglobin (HbA1c) levels to determine glycemic control status, along with blood pressure measurements. The data were analyzed using the Independent Samples t-test in JASP software. The statistical analysis revealed a significant difference in systolic blood pressure (p = 0.020) and diastolic blood pressure (p = 0.039) between the controlled and uncontrolled groups. Patients with uncontrolled HbA1c levels exhibited higher systolic and diastolic blood pressure compared to those with controlled HbA1c levels. These findings highlight the importance of routine HbA1c monitoring in primary healthcare settings to prevent hypertension among patients with T2DM. In conclusion, glycemic control status may serve as a significant predictor of blood pressure levels in patients with type 2 diabetes mellitus.Keywords: blood pressure; type 2 diabetes mellitus; glycated hemoglobin; hypertension; primary healthcare centers